The Middle East and COVID-19: time for collective action - Louise Fawcett (BMC, 2021)
Abstract Revised: Nov 6 2021 The shortfalls of multilateral and regional organizations in respect of handling the COVID-19 pandemic have been well rehearsed by scholars and policy makers in multiple publications and statements. While the World Health Organization (WHO) and its regional offices have coordinated global responses, regional organizations, like the European Union, Association of Southeast Asian Nations, or African Union, have played complementary roles. However, the response of different regions has varied, revealing multiple deficits in the structures of regional governance. The Middle East and North Africa (MENA) is a region affected by chronic ongoing conflicts and serious inequalities in health and welfare provision, reflected in the absence of concerted responses to the pandemic. Its young population has meant lower comparative mortality rates, but the socio-economic spill-over effects are grave in terms of interrupted education, high unemployment, particularly in respect to vulnerable communities like refugees and migrant workers. With the current situation remaining critical, this paper reviews the impact of COVID-19 on MENA and considers the variable performance of states and institutions to the pandemic, highlighting the shortfalls, but also opportunities for collective action. Drawing on data from the WHO, United Nations (UN), regional organizations, media and secondary sources, it first discusses the wider global-regional context; second, reviews the actions of regional bodies, like the League of Arab States, Gulf Cooperation Council and the cross-regional Organization of Islamic Cooperation; and third, looks at some country-specific situations where both evidence of good practice and the absence of appropriate regional level provision have exposed deep regional divides. It concludes with a call for more collaboration between states and international organizations: better regional coordination is urgently needed to supplement existing multilateral efforts. A collective local response to the COVID-19 pandemic could help transcend regional divides and spur much-needed security cooperation in other areas.